Penerapan Terapi ABA dalam Meningkatkan Komunikasi dan Interaksi Anak Autis Kelas II di SDK Santamaria Asumpta Kota Kupang (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the application of Applied Behaviour Analysis (ABA) therapy in improving communication and interaction skills through eye contact in children with autism at SDK Santa Maria Assumpta, Kupang City. The problems underlying this study are the children's low focus when communicating, difficulty responding to calls, and minimal eye contact when receiving instructions. The study used a descriptive qualitative approach. Data collection was conducted through participatory observation of the therapy implementation and interviews with therapists and school officials. Data were analysed using the stages of data reduction, data presentation, and conclusion drawing. ABA was implemented through focus training with word and movement imitation, directing the child's head to establish eye contact with the therapist, and giving simple instructions that were gradually increased. Each appropriate response was reinforced through verbal praise. The results of the study showed that the application of ABA therapy was able to increase the duration and consistency of eye contact, imitation skills, compliance with instructions, and the development of basic academic skills such as writing and puzzle solving. These findings indicate that ABA therapy is effective as a structured intervention to support the development of communication and interaction in children with autism in primary school settings.